Unveiling the Stimulated Robust Carrier Lifetime of Surface‐Bound Excitons and Their Photoresponse in InSe. Issue 13 (6th May 2019) - Wang, Rui; Jiang, Xiantao; Gao, Siyan; Zhao, Jinlai; Zhang, Feng; Huang, Weichun; Fan, Taojian; Liang, Weiyuan; Li, Zhongjun; Huang, Hao; Guo, Zhinan; Wang, Huide; et al.
Abstract: In contrast to zero‐bandgap metallic graphene, the binary semiconducting compound, InSe, possesses a tunable bandgap. Herein, a range of particle sizes of β‐InSe from bulk to few‐layer nanosheets and quantum dots are carefully prepared. The size‐dependent bandgap variation and photon‐induced carrier dynamics of InSe are systemically investigated. In contrast to the normal size‐dependent carrier lifetime trend observed at 700 nm, anomalous size‐independent carrier decay is observed at 500 nm. Through time‐dependent density functional theory calculations, the normal carrier lifetimes at lower probe photon energies are attributed to in‐plane excitons, whereas the abnormal size‐independent carrier lifetimes at higher probe photon energies are found to be stimulated by surface‐bound excitons. In view of the robust surface exciton, this suggests that InSe may possess an outstanding optoelectronic performance in the shorter wavelength range. Through photoelectrochemical detection experiments, it is confirmed that InSe features a high photocurrent density and stability and, in particular, a more distinct photoresponse at short wavelengths than at longer ones. Comprehending and quantifying the role of the surface‐bound excitons in InSe across a broad range of semiconductor nanostructures and their fundamental properties may play an important role in understanding the physical properties of 2D III–VI compound materials. Abstract : The binary InSe compound has a tunable bandgap. The size‐dependent band gap variation and carrier dynamics of InSe are systemically investigated. Through time‐dependent density functional theory calculations, normal carrier lifetime for the long wavelength range is attributed to in‐plane excitons, whereas the abnormal size‐independent carrier lifetime for the short wavelength range is stimulated by surface‐bound excitons.